PERAN PEMERINTAH DAERAH MENINGKATKAN PARTISIPASI MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN DI KABUPATEN NAGAN RAYA - Sri Wahyu Handayani (Jurnal Public Policy, 2018)
Implementation of Law Number 28 Year 2009 About Local Taxes and Levies and Qanun of Nagan Raya Regency Number 13 Year 2011 About Land Tax Rural and urban sector buildings have regulated the tax system of rural and urban land building taxes that were originally a central tax now become tax region, this is a form of follow-up of regional autonomy and existing fiscal decentralization. The result of the tax management 100% (one hundred percent) goes to the local treasury so that there is no more tax revenue sharing to the central government. One of the supporting aspects of success is through community participation. This study aims to determine how the role of government in every process of making policy, strategy, communication dispute resolution and role as therapy in society. This research uses qualitative descriptive method, based on the data obtained from the results of this study is described with the sentence according to the category to conclude, the data in the form of observation, interview and documentation.The results of this study indicate that the role of local government to increase the participation of the people paying the rural and urban land tax building is done through efforts such as improving the tax and retribution services through the simplification of administrative systems and procedures, raising public awareness through socialization approach, impose a 2% penalty per month for taxpayers who are late in paying taxes on PBB-P2, improving the quality of employees or tax collectors, improving and structuring the procedures of the financial administration system to prevent errors, leaks or deviations from the use of funds thereby through efforts made by the Regional Government Nagan Raya District is running well. This can be proven through data obtained by researchers through the Regional Finance Management Agency of Nagan Raya District, the increase of the number of taxpayers and the UN-P2 revenue from 2014-2016 in Nagan Raya District.Keywords : The role, local government, public participation, tax land sector buildingrural and urban areas